2006
DOI: 10.1021/ja058214+
|View full text |Cite
|
Sign up to set email alerts
|

Selective Interaction of Large or Charge-Transfer Aromatic Molecules with Metallic Single-Wall Carbon Nanotubes:  Critical Role of the Molecular Size and Orientation

Abstract: Using first principles calculations, we report for the first time that large nearly neutral aromatic molecules, such as naphthalene and anthracene, and small charge-transfer aromatic molecules, such as TCNQ and DDQ, interact more strongly with metallic single-wall carbon nanotubes (SWNTs) versus their semiconducting counterparts as the molecular orientation of DDQ is taken into account. Hence two new mechanisms for separating metallic and semiconducting SWNTs via noncovalent pi-pi stacking or charge-transfer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 21 publications
10
134
0
2
Order By: Relevance
“…41 Indeed, Beless et al demonstrated that substituted biphenyl compounds, such as those in E7, are able to adsorb efficiently onto carbon nanotubes provided the aromatic rings were not sterically hindered against entering a plane with each other. 42 The electron deficient cyano group, present on all the components of E7, are known to interact with SWCNTs 43,44 via the formation of a charge transfer complex. Harrison et al reported cyano-SWCNT charge-transfer complexes to be the cause on upshifts in the SWCNT G band of þ4 cm…”
mentioning
confidence: 99%
“…41 Indeed, Beless et al demonstrated that substituted biphenyl compounds, such as those in E7, are able to adsorb efficiently onto carbon nanotubes provided the aromatic rings were not sterically hindered against entering a plane with each other. 42 The electron deficient cyano group, present on all the components of E7, are known to interact with SWCNTs 43,44 via the formation of a charge transfer complex. Harrison et al reported cyano-SWCNT charge-transfer complexes to be the cause on upshifts in the SWCNT G band of þ4 cm…”
mentioning
confidence: 99%
“…We tentatively ascribe this discrepancy to a toluene solvent effect in the experiment, since a gas phase model is The calculated selectivities of the three nanotweezers for the zigzag tubes versus the armchair tubes are attributed to the fact that the hexagonal carbon ring of the three nanotweezers is identical with (matches) that on the zigzag tube sidewall. Our previous calculations [22,23] demonstrate that the alignment between the hexagonal ring of planar aromatic molecules and that of SWNTs can stabilize the adsorption (by atomic correlation effects). Since the hexagonal rings of the anthracene-, pentacene-, and heptacene-based nanotweezers are aligned with those on the sidewall of zigzag SWNTs, these three molecules all prefer to attach to the zigzag SWNTs.…”
Section: Resultsmentioning
confidence: 96%
“…In fact, the LDA has been widely used to study the π-π stacking interaction between molecules and SWNTs [31,33,34] and in other large systems [30,35]. We use the LDA to study the interaction between aromatic moleculebased nanotweezers and SWNTs, inspired by the fact that the our previous LDA calculations [22,23] correctly predicted the selectivity of planar aromatic molecules towards SWNTs [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As CNTs are hollow, it is also possible to incorporate dopants within the interior of the CNT, i.e., endohedral doping. Endohedral dopants, such as fullerenes, 24 metallocenes, 25 and organic molecules, 24,[26][27][28][29][30] relevant CNTs. Idealized nitrogen and boron doped CNTs (i.e., we assume no additional defects) are considered for pand n-type doping, respectively, along with the endohedral dopant tetrathiafulvalene (TTF) which is known to induce ntype doping in CNTs and is stable in atmosphere.…”
Section: Formation Of Contacts Between Doped Carbon Nanotubes and Alumentioning
confidence: 99%